Treaty-Based Claims Against Subdivisions of ICSID Contracting States - Douglas Pivnichny (Washington University Global Studies Law Review, 2017)
This article primarily concerns the juridical personality of States in public international law, how this has changed in the 20th century, and potential consequences of these developments in the field of investor-State arbitration. Specifically, it asks whether a subdivision of a federal State made subject to the jurisdiction of the International Centre for the Settlement of Investment Disputes (“ICSID” or “the Centre”) under Article 25 of the ICSID Convention may be responsible as a juridical person independent of its State for violating an investment treaty (e.g., a bilateral investment treaty (“BIT”) or the investment chapter of a free-trade agreement (“FTA”)) to which that State is party. This article will first briefly address the possibility of the application of a BIT to a subdivision by an ICSID tribunal as applicable domestic law. At issue here is not the juridical personality of the subdivision, which typically exists in the domestic law of the parent States. Instead, the threshold question will be whether the applicable domestic law has incorporated the substantive standards in the BIT.
Keywords: juridical personality; public international law; investor-state arbitration; ICSID; bilateral investment treaty; BIT; FTA; free-trade agreement; non-state entities; international criminal law; legal personality; third party effect; opposability; sovereign competence theory